Power compensation and Voltage flicker control of Solar-wind hybrid microgrid with optimized D-STATCOM using a control Technique - Khan, M.M.H. (Institute of Electrical and Electronics Engineers Inc., 2022)
Distributed Generation (DG) nowadays is becoming increasingly significant in electricity generation Constructively increase of Wind Turbine systems (WTs) and Solar Photovoltaic (PV) integration with electricity grid has an impact on stable operation of the grid transmissions. Wind and PV generation are highly intermittent. Its intermittency contribution will bring changes in Wind and PV generation performance. Therefore, it is becoming progressively important for electrical grid operator to maintain a stable and reliable operation of electricity transmission and distribution systems. For Power Quality (PQ) disturbances to be compensated, an alternative techniques of power technology is required. DG's systems have shown that their power transformers and optimization techniques can contribute to grid stability. In order to maintain effective adaptation efficiency and grid stability, A Flexible Alternating Current Transmission system (FACTs) technologies must also be implemented. D-STATCOM is used to improve the PQ as one of them the electronic power instruments. By reducing PQ fluctuations, the functionality of D-STATCOM must be optimized. This research reveals a Solar PV-Wind Integrated Microgrid framework and explores an improvement in the system's stable operating limit in the event of implementation of D-STATCOM. The crucial effects of DG grid interaction and the function of D-STATCOM in mitigating unexpected results and improving the reliability of the DG into full operation are present in this paper. D-STATCOM controlling technique for monitoring the stability of electrical grid has been proposed and demonstrating the effect of this system on electricity grid. The strength of the methodology suggested is to increase the stability of electricity grid in continuous grid operation and under varying operating conditions. In addition, increases the reliability of transient voltage 4.2, Improvement of voltage and current flicker and reduces 54.5 harmonic disturbances. Â© 2022 IEEE.